2020
DOI: 10.3390/biomedicines8080272
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Endosomal Intoxication: A Balance between Exosomes and Lysosomes at the Basis of Intercellular Amyloid Propagation

Abstract: In Alzheimer′s disease (AD), endolysosomal dysfunctions are amongst the earliest cellular features to appear. Each organelle of the endolysosomal system, from the multivesicular body (MVB) to the lysosome, contributes to the homeostasis of amyloid precursor protein (APP) cleavage products including β-amyloid (Aβ) peptides. Hence, this review will attempt to disentangle how changes in the endolysosomal system cumulate to the generation of toxic amyloid species and hamper their degradation. We highlight that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 207 publications
2
14
0
1
Order By: Relevance
“…We next investigated the mechanisms by which loss of retromer results in increased levels of EV cargo. Since retromer is required to maintain lysosomal hydrolase activity ( Arighi et al, 2004 ; Cui et al, 2019 ; Seaman et al, 1998 ), general lysosomal dysfunction in retromer mutants might lead to the accumulation and release of material that would otherwise be targeted for degradation ( Bécot et al, 2020 ). We tested this by examining the lysosomal marker Spinster (Spin; Dermaut et al, 2005 ; Sweeney and Davis, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the mechanisms by which loss of retromer results in increased levels of EV cargo. Since retromer is required to maintain lysosomal hydrolase activity ( Arighi et al, 2004 ; Cui et al, 2019 ; Seaman et al, 1998 ), general lysosomal dysfunction in retromer mutants might lead to the accumulation and release of material that would otherwise be targeted for degradation ( Bécot et al, 2020 ). We tested this by examining the lysosomal marker Spinster (Spin; Dermaut et al, 2005 ; Sweeney and Davis, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our results suggest new interpretations of neurological disease mechanism. Defects in EV and endosomal trafficking are linked to neurodegenerative diseases such as Alzheimer’s Disease (Becot et al, 2020; Song et al, 2020; Winckler et al, 2018). Aged neurons exhibit increased APP endocytosis, leading to endosomal dysfunction and synapse loss (Burrinha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…7c). It has been reported that amyloid-beta A4 precursor proteinbinding family A member 2 (APBA2) is involved in synaptic transport and junction of neurons [35], but they are also involved in improving immunity and cell regeneration [36]. We hypothesized that the antiin ammatory effect of HMEECs was increased by the expression of miRNA-638 in H:BM-M and APBA2 could be expected to be a candidate connection protein (Fig.…”
Section: The Amyloid-based Binding Proteins Combined To Decrease In Amentioning
confidence: 99%